A Self-Gravitating Exoring Around J1407b and Implications for In-Situ Exomoon Formation - Sutton, Phil J; Albery, Brayden; Muff, Jake (Frontiers in Astronomy and Space Sciences, 2022)
We perform simulations of the M_⊕ self-gravitating exoring thought to orbit the large exoplanet J1407b. We use a mass of M_J1407b=20M_J(which is close to the revised upper limit) and a semi-major axis of a=5AU, equating to an orbital period of ~11yrs about the primary. As J1407b is expected to have a high eccentricity, we test eight different models: where e=0.2, 0.4, 0.6 & 0.8 in both the prograde and retrograde configurations. All prograde models show a strongly perturbed ring within the first orbit. As expected, the retrograde rings demonstrate a higher degree of stability, with the lower eccentricity models (e=0.2 & 0.4) able to survive multiple orbits. However, even the higher eccentricity (e=0.6 & 0.8) retrograde models quickly result in the loss of the ring after 200 years. Excitation of eccentricities in all retrograde rings are stable to gravitational collapse. Thus, at least for the lower mass limit, the ring is unfavorable to the accretion of moons when J1407b is on an elliptical orbit. An interesting consequence of the strong perturbation for one model (retrograde & e=0.6) during the first close passage is a transient gap located at 0.4AU. This is the same location as the inferred gap from the single transit in 2007 and does not require a nearby exomoon.